2020
DOI: 10.1002/psp.2365
|View full text |Cite
|
Sign up to set email alerts
|

Transnational ageing and “care technologies”: Chinese grandparenting migrants in Singapore and Sydney

Abstract: Transnational grandparenting examines the care that grandparents provide across borders, recreating familyhood. This paper investigates how Information Communication Technologies (ICT) mediate ageing in localised and transnational contexts. We focus on grandparenting migrants from the People's Republic of China who moved temporarily to Singapore and Sydney, Australia. We introduce the concept of "care technologies" to explicate two dimensions of governmentality. The first dimension considers how governmentalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Through the medium of WeChat, Mrs. Ma remains in touch with her Perth social networks and their quotidian concerns, joys and crises, and so each time she returns to Australia, as with each return journey to China, she picks up friendships as though no time had passed. Like other members of this cohort, Mrs. Ma relies on digital technologies for their enabling functions, supporting daily life, as well as their capacity to sustain care practices across distance (Ho & Chiu, 2020; Nedelcu, 2017), allowing her to participate digitally in affective economies (Wilding et al, 2020) that extend beyond her family to wider networks of friends.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the medium of WeChat, Mrs. Ma remains in touch with her Perth social networks and their quotidian concerns, joys and crises, and so each time she returns to Australia, as with each return journey to China, she picks up friendships as though no time had passed. Like other members of this cohort, Mrs. Ma relies on digital technologies for their enabling functions, supporting daily life, as well as their capacity to sustain care practices across distance (Ho & Chiu, 2020; Nedelcu, 2017), allowing her to participate digitally in affective economies (Wilding et al, 2020) that extend beyond her family to wider networks of friends.…”
Section: Case Studiesmentioning
confidence: 99%
“…Compared to their older counterparts, the younger cohorts’ relative digital access and literacy affords them greater “digital anticipation,” by which we mean the ability to imagine futures supported by digital engagement. Ho and Chiu (2020) have shown that the co-constitution of ICTs and care relations as “care technologies” help grandparent migrants to endure the challenges of maintaining family life across borders. Similarly, our case studies demonstrate that these same technologies form an integral part of the ability to anticipate aging futures, with the younger cohorts’ relative digital access and literacy affording them greater “digital anticipation” in the form of an ability to proactively pre-empt futures supported by digital engagement.…”
Section: Introductionmentioning
confidence: 99%
“…work, school and childcare) (Rodriguez Castro et al, 2020). Rhythms of everyday domestic routines and family life relate to wider moral beliefs about the ideal order of society, including expectations of women’s domestic labour (Holdsworth, 2020) and intergenerational relations (Ho and Chiu, 2020). Blunt et al’s (2020) focus on ‘home-city biographies’ also remind us of how intimate space-times extend across multiple, co-existing scales.…”
Section: Intimate Space-times Life Stage and Life-coursementioning
confidence: 99%
“…Overall, it could be argued that home can be everywhere and anywhere so long as these feelings and kinships are maintained, although some societal changes or events such as the digital revolution or the current COVID‐19 pandemic might provide some limitations to this statement. For example, studies of Ho and Chiu (2020) have shown that digital technology is an important tool for older Chinese immigrants to maintain their social networks in the transnational context, whereas research of Matthews (2020) and Gezici Yalçın and Düzen (2021) suggested that daily lives and habits in the city such as social activities and transportation were threatened by COVID, which alter people's sense of home.…”
Section: The Concept Of Homementioning
confidence: 99%